quality of placements during the pandemic and the applicable sanitary regime as assessed by physiotherapy students from Poland - Agnieszka Jankowicz-Szymańska; Anna Stefanowicz-Kocoł; Aneta Grochowska (University of Applied Sciences in Tarnow, Poland, 2022)
Introduction: The COVID-19 pandemic and the related sanitary rigour pose a great challenge for universities preparing young people to work in medical and medicine-related professions, including the profession of a physiotherapist. It is particularly difficult to conduct placements, during which both students and employees of the institution as well as patients will be provided with maximum safety, but at the same time high standards of education will be maintained. The aim of the study was to assess possible changes in the quality of placements that might have occurred during the COVID-19 pandemic and the applicable sanitary regime. Material and methods: The study was conducted in October 2021 among 67 students of physiotherapy at the University of Applied Sciences in Tarnow, Poland. The sample consisted of both women (n = 49) and men (n = 18) who had completed at least one full work placement prior to the outbreak of the pandemic and at least one full work placement during the pandemic. Students voluntarily filled in a purpose-built electronic questionnaire, in which they responded to 20 questions referring the conditions of placements, cooperation with staff, the atmosphere in the institution and the skills acquired there. They determined on a scale of 1 to 5 (1 - has definitely changed in favour, 5 - has definitely changed in an unfavourable way), how professional practices have changed due to the pandemic and the sanitary regime. Students could also add their comments in the form of recommendations aimed at improving the quality of placements. They were invited to do it with the following statement: Provide an example of a practical solution that would help improve the quality of placements. Results: According to the respondents, the most unfavourable changes in the quality of placements caused by the pandemic are: increased stress related to placements, worse conditions for learning how to diagnose and plan therapy, limited opportunities to learn about modern methods of therapy and limited opportunities to work directly with the patient. The respondents also noticed positive changes in the quality of placements. These were the opportunity to work in a small group, a better atmosphere in the institution, more help from the staff and better familiarization with the place of the placement. Conclusions: The pandemic has brought both positive and negative changes in the quality of placements. Monitoring the quality of placements and surveying students' opinions is a very important tool in improving the quality of education. It is worthwhile to carry out extra quality control studies at times of change to be aware of possible changes in the quality of placements induced by such challenging situations. It was also interesting to notice that students expect some of the changes related to the sanitary regime to persist after the pandemic has ended.